Estimativa da Evapotranspiração Potencialem Bagé-RS para Aplicação no Indice Padronizado Precipitação-Evapotranspiração - Goergen, Guilherme; Tatsch, Jônatan Dupont; Moraes, Marcelo Romero de (Ciência e Natura, 2013)
The aim of this study was to evaluate the best method for estimating potential evapotranspiration for the region of Bagé-RS, for its application in standardized precipitation evapotranspiration index (SPEI). Among the methods evaluated, the Penman-Montheith (ET0pen) presented the best estimates compared to measured potential evaporation. The use of ET0pen on index calculation SPEI identified drought periods consistent with those reported in the media.